Structural, specific heat and magnetoresistive properties of Gd0.7Ca0.3MnO3. (1st January 2014) - Negi, P.; Agrawal, H.M.; Srivastava, R.C.
Here, we report the structural, specific heat and magnetoresistive properties of orthorhombic perovskite structured Gd0.7 Ca0.3 MnO3, synthesised by modified sol-gel technique. X-ray diffraction along with the Rietveld refinement confirms the pure phase of the sample and the crystallite size comes out to be ~42 nm. Scanning electron micrograph shows the grain distribution having average particle size ~71 nm. Energy dispersive spectroscopy confirms the stoichiometry of the composition. The sample is also characterised by Raman spectroscopy for structural and phase confirmation. The functional group of Gd0.7 Ca0.3 MnO3 was also analysed from its Fourier transform infrared (FTIR) spectrum. The specific heat of the sample is measured in the temperature range of 2 to 300 K. Resistivity measurements with and without magnetic field was performed. The activation energy in absence of magnetic field is 0.162 eV which reduces to 0.154 eV in presence of 8 T magnetic field. The observed electrical behaviour is explained in terms of polaron hopping mechanism.